Identification of Locus GH/Alui Polymorphisms of Kuantan and Pesisir Cattle - Hidayati Hidayati; Robbana Saragih (Buletin Peternakan, 2020)
Kuantan cattle is a local beef cattle of Riau Province that adaptive and breed well along the Kuantan river flow, found in Indragiri Hulu Regency and Kuantan Singingi Regency, have smaller morphometric performance compared to other local beef cattle and are relatively the same as Pesisir cattle. One of the genetic markers of growth determinant in beef cattle is the GH/AluI gene locus. Identification of the diversity of the GH/Alu I gene was carried out using the PCR-RFLP. Fifty four samples of Kuantan cattle consisting of 25 samples from Indragiri Hulu Regency and 29 samples from Kuantan Singingi Regency, as well as 25 samples of Pesisir cattle from BPTU-HPT Padang Mengatas Payakumbuh, West Sumatra, were used in this study. The oligonucleotida forward F-5’GCTGCTCCTGAGGGCCCTTC-3’ and reverse R-5’CATGACCCTCAGGTACGTCTCCG-3’ used in this study along 211 bp of GH Gene. The PCR mixture consisted of DNA templates 20 - 25 ng, 0.4 µL  primer forward dan primer reverse (10 ng primer forward and primer reverse), 25 µL dream tag green master mix and ddH2O up to a 50 µL. PCR machine conditions consisted of 940C pradenaturation for 5 minutes, 940C denaturation for 30 seconds, annealing 650C for 1 minute, 720C extension for 50 seconds and 720C final extension for 5 minutes. Identification of GH gene diversity using AluI at an incubation temperature of 370C for 3 hours. The results in this study were found monomorphic of GH/AluI genes in Kuantan and Pesisir cattle. The monomorphic in Kuantan cattle can be used as an indicator to assess the purity of Kuantan cattle in this areas.